Analysis of Tax Accounting Implementation at Pt. Pou Yuen Indonesia - Mutiara, Indah; Saputra, Arip (Yayasan Meira Visi Persada, 2024)
With the increasing number of companies in the industrial sector in Indonesia, of course the government is increasingly aggressively implementing various regulations to control and accommodate the rights and obligations that must be given to each company. And one of the lines that must be considered is the issue of taxation, which is also an important factor for the sustainability of company activities. Because every activity carried out by the company certainly cannot be separated from the tax rules that must be met, both when purchasing goods, paying employee wages and so on. Therefore, this research aims to analyze what tax accounting is applied at PT Pou Yuen Indonesia to find out the extent of government regulations that can be implemented by companies that have various accounting activities related to taxation.